The effect of syncope on brain natriuretic peptide. Issue 12 (3rd February 2011) - Reed, Matthew J; Gibson, Louise
Abstract : Background: Brain natriuretic peptide (BNP) may be a good prognostic marker in syncope. The aim of this study was to establish whether there is any change in BNP in association with an acute presentation. Methods: Patients aged ≥60 years admitted following presentation to the emergency department (ED) with syncope were eligible for prospective enrolment. Serial BNP measurements were performed on admission and at intervals up to 4 weeks after presentation. Results: Between 8 March 2010 and 14 April 2010, 31 patients were recruited and were suitable for analysis, including seven patients who returned to the ED at 4 weeks. Mean BNP rose from a baseline of 167.8 ng/ml to a peak of 303.2 ng/ml at 48 h and then returned to baseline at 4 weeks. BNP ratio reached 2.3 (more than twice admission level) at 18 h and peaked at 2.4 at 1 week before returning to baseline at 4 weeks. Conclusions: BNP seems to rise from baseline to a peak between 18 h and 1 week after an acute syncopal episode in many patients. The reasons for this are not clear.